The pH of guinea pig (Cavia porcellus) meat from the welfare-deficient slaughtering in the Peruvian central Andes (FAVE Sección Ciencias Veterinarias, 2017)
In Andean region of Peru is common to slaughter Guinea pig without lairage and stunning. The aim of this study was to evaluate the pH of meat of Guinea pig (Cavia porcellus) from the unsuitable welfare practices during slaughtering in the Peruvian central Andes. The pH of 60 guinea pig carcasses were analyzed at 0, 1, 6, 12 and 24 hours after the end of the slaughter process. The pH was 6.79 ± 0.3, 6.74 ± 0.34, 6.59 ± 0.28, 6.45 ± 0.35 and 5.96 ± 0.11 for 0, 1, 6, 12 y 24 h post slaughtering. The equation that graphs pH evolution was Y=6.7765-0.0231X-0.0005X2 (R2=0.996).
Keywords: pH; guinea pig; slaughterhouse